The Influence of Self-Relevance and Cultural Values on Moral Orientation - Bian, Junfeng; Li, Liang; Sun, Jianzhou; Deng, Jie; Li, Qianwei; Zhang, Xiaoli; Yan, Liangshi (Frontiers in Psychology, 2019)
Moral orientation refers to moral values that have a consistent guiding orientation towards an individual’s moral cognition and behavior. Gilligan (1982) proposed that individuals have two moral orientations, namely “justice” and “care.” In the current study, we investigated the influence of self-relevance and cultural values on justice and care by using Single Attribute Implicit Association Test (SA-IAT). In Experiments 1 and 2, we adopted cultural icon prime paradigm to examine the effects of different self-referential stimuli (self, friend, and stranger) on implicit moral justice and care orientation under two cultural value conditions: traditionality, modernity, and neutral cultural values. Participants exhibited more difference toward different self-referential stimuli in the traditionality condition than in the modernity condition; the priming of traditional culture aggravated the differential order, whereas the priming of modernity weakened the differential order regarding implicitly just moral orientation. In the implicit care orientation, participants in the modern culture group exhibited the least difference to different self-referential stimuli compared with the other two groups, and the traditional group and the control group did not differ significantly. These findings indicate that psychological modernity weakens the degree of self-related effect in implicit justice and care orientation, whereas traditional culture aggravates the differential order in justice orientation. The current studies provide empirical support for theories relating moral orientation, also informing the literature on the role of self-relevance information and cultural values in moral decision making. Keywords: Moral orientation, justice, care, degree of self-reference, differential effect, cultural value